(untitled) (World Bulletin of Public Health, 2022)
This article presents the results of the introduction of innovative methods for the diagnosis of allergic dermatoses in the Khorezm region. The increase in the incidence of allergic dermatitis is associated with the adverse effects of certain environmental factors. The most resistant to treatment and often recurrent forms of the disease are clinical forms in which there is sensitization to various bacterial factors, in particular to Staphylococcus spp.